Dampak Belanja Pemerintah Terhadap Ketimpangan Ekonomi - Hana Malika Rahmah Sitorus; Nabila Putri Wirani; Zhafira Syaifani Siregar; Ahmad Wahyudi Zein (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the impact of government spending on economic inequality in Indonesia. Government spending plays an important role in social and economic development, through allocations to the education, health, and infrastructure sectors. Although this spending can make a positive contribution to reducing inequality through income redistribution and equitable development, negative impacts can also occur if spending is not on target, accompanied by corrupt practices or regressive fiscal policies. Using a qualitative descriptive approach, this study describes how the characteristics and effectiveness of government spending affect the inequality of economic distribution and public welfare. The findings of this study indicate the importance of budget policy reform to be more inclusive, on target, and transparent in order to create equitable development.